2005
DOI: 10.1164/rccm.200502-286oc
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Changes during the Development of Acute Lung Injury Role of Transforming Growth Factor β

Abstract: Rationale: Acute lung injury can occur from multiple causes, resulting in high mortality. The pathophysiology of nickel-induced acute lung injury in mice is remarkably complex, and the molecular mechanisms are uncertain. Objectives: To integrate molecular pathways and investigate the role of transforming growth factor ␤ (TGF-␤) in acute lung injury in mice. Methods: cDNA microarray analyses were used to identify lung gene expression changes after nickel exposure. MAPPFinder analysis of the microarray data was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 87 publications
0
58
0
Order By: Relevance
“…12 TGF-b1 is a multifunctional cytokine that has a vital role in modifying lung permeability, epithelial ion transport, fibrinolysis, ECM deposition and surfactant homeostasis and can induce the cytoskeletal reorganization observed in EMT. 11 A previous study of patients with lung fibrogenesis revealed that engaging the avb6 integrin of epithelial cells to fibronectin may trigger the activation and production of TGF-b1. 10 Moreover, epithelial cells can promote lung fibrogenesis by acquiring a mesenchymal phenotype through the mediation of TGF-b1.…”
Section: Discussionmentioning
confidence: 99%
“…12 TGF-b1 is a multifunctional cytokine that has a vital role in modifying lung permeability, epithelial ion transport, fibrinolysis, ECM deposition and surfactant homeostasis and can induce the cytoskeletal reorganization observed in EMT. 11 A previous study of patients with lung fibrogenesis revealed that engaging the avb6 integrin of epithelial cells to fibronectin may trigger the activation and production of TGF-b1. 10 Moreover, epithelial cells can promote lung fibrogenesis by acquiring a mesenchymal phenotype through the mediation of TGF-b1.…”
Section: Discussionmentioning
confidence: 99%
“…SEMA7A polymorphisms are associated with abnormal bone mineral density in Korean women (72). During acute lung injury, TGFB1 can increase endothelial and epithelial permeability (73)(74)(75), and the inhibition of TGFB1 can diminish lung injury (66,(76)(77)(78). SEMA7A can mediate AKT phosphorylation (71), which is …”
Section: Discussionmentioning
confidence: 99%
“…During gross pathologic observations at death, the lung surface appeared red from hemorrhaging and coagulation consistent with severe lung injury (66). The mean survival time was distributed continuously among murine strains (supportive of a complex trait), with the polar strains varying by approximately 5-fold from 7.6 6 0.8 (mean 6 SEM) hours (PWD/PhJ) to 38.1 6 0.5 hours (NON/ShiLtJ) ( Figure 1A).…”
Section: Haplotype Mapping Of Survival Times In 40 Murine Strainsmentioning
confidence: 92%
“…For example, the inhalation of nickelcontaining substances has been shown to be linked to a rise in Transforming Growth Factor Beta (TGF-B) levels, yielding morphological changes in the lung tissue. These changes to the lung tissue may also result in respiratory failure [11] . Inflammation of the lung tissues as a result of inhaled toxins is also considered to be a lung cancer risk factor [4] .…”
Section: Introductionmentioning
confidence: 99%